Analisis pelaksanaan pembelajaran berdiferensiasi untuk meningkatkan literasi numerasi siswa di sekolah dasar - Samsiyah, Siti (Jurnal Pendidikan Dasar, 2022)
Literacy and numeracy are the main components in the Minimum Competency Assessment as a substitute for the national exam. Literacy and numeracy skills are very important for students because they are related to the 21st-century learning process, which involves critical thinking skills in solving problems in everyday life. There are several options to improve students' understanding of numeracy literacy, one of which is to apply a differentiated learning strategy through STAR. The purpose of this research is to describe the analysis of the implementation of differentiated learning to improve the literacy skills of elementary school students. The method used is a qualitative approach with descriptive methods. In a case study at SDN Kleco II Surakarta for the 2021/2022 academic year. The results showed that the implementation of differentiated learning through STAR conducted by researchers improved students' numeracy literacy skills at SDN Kleco II Surakarta.